CAECIDAE GASTROPODS FOUND IN BEDS OF THE MUSSEL Perna perna (BIVALVIA: MYTILIDAE), ON THE ROCKY SHORES OF BENEVENTE BAY, ESPÍRITO SANTO STATE - da Silva, Clésio Castro; de Castro, Gilson Alexandre (Arquivos de Ciências do Mar, 2014)
Studies were conducted for the first time on the abundance and composition of the stages of development of gastropod mollusks of the family Caecidae in living beds of the mussel Perna perna from the rocky shores of Benevente Bay, located on the southern coast of Espirito Santo State. Developmental stages of Caecum ryssotitum and Caecum jucundum were found in the mussel’s beds demonstrating the existence of microhabitats to enhance the survival of those microgastropods.